482 Dressler's syndrome following catheter ablation of atrial fibrillation: a case series. (8th December 2021) - Magnocavallo, Michele; Rocca, Domenico Giovanni Della; Lavalle, Carlo; Chimenti, Cristina; Carola, Gianni; Mohanty, Sanghamitra; Trivedi, Chintan; Bassiouny, Mohamed; Al-Ahmad, Amin; Burkhardt, David J; Gallinghouse, Joseph G; Sanchez, Javier E; et al.
Abstract: Aims: Dressler's syndrome is a secondary form of pleuro-pericarditis caused by an immune system response to heart damage. The onset of Dressler's syndrome following catheter ablation has been previously described in rare case reports. We sought to report clinical manifestations, management, and outcomes of Dressler's syndrome after atrial fibrillation (AF) catheter ablation. Methods and results: Data from five AF patients who underwent radiofrequency ablation that was complicated by the development of Dressler's syndrome were extracted from a prospective, single-centre database. Five out of 12 747 patients (0.04%) developed Dressler's syndrome post AF ablation, 100% of which were females, with a mean age of 75.8 ± 3.4 years. All patients had persistent AF, and had pulmonary vein (PV) antrum, plus posterior wall isolation, plus non-PV trigger ablation. The mean procedure, fluoroscopy, and radiofrequency times were 183.20 ± 48.0, 50.3 ± 24.0, and 78.03 ± 27.9 min, respectively. All procedures were uncomplicated, and patients were discharged after overnight observation. Hospital re-admission was required in all after an average of 13.2 ± 5.2 days, due to worsening dyspnoea, pleuritic pain, and low-grade fever. At re-admission, all five patients had moderate-severe leucocytosis with neutrophilia, as well as bilateral rales and pericardial friction rub. Transthoracic echocardiography showed a mean pericardial circumferential effusion of 8 ± 2 mm, and chest X-ray was suggestive of bilateral mild pleural effusion in all. Corticosteroids were prescribed in three and NSAIDs plus colchicine in two patients. Pericardial drain placement was required in three patients after a median of 3 days, due to increasing pericardial effusion with hemodynamic impairment. The drainage tube was removed after a median of 2 days. All patients had complete resolution of symptoms and remained free from pericardial/pleural effusion within 1-month post-admission. Four of five patients had repeat ablation without recurrent Dressler's syndrome. Conclusions: Dressler's syndrome occurred in older female patients, who underwent extensive ablation for AF. If promptly treated, its clinical course appears favourable with complete resolution of symptoms and pleuro-pericardial involvement.